Analisis Periode Rotasi Matahari Berdasarkan Pergerakan Bintik Matahari AR 4207 pada Citra SolarHam Tanggal 1–8 September 2025 - Rustaman; Rodika Utama (JURNAL ARMADA PENDIDIKAN, 2026)
This study aims to determine the rotational period of the Sun by analyzing the motion of a sunspot across the solar disk. The active sunspot region AR 4207 was examined using solar continuum images acquired on 1 and 8 September 2025. The position of the sunspot on each date was projected onto a circular diagram with the central meridian as the reference axis in order to measure its angular displacement. The projected angles relative to the central meridian were found to be  on 1 September and  on 8 September, yielding a total displacement of  over a seven-day interval. By applying the relation , the solar rotation period was calculated to be  days. This result aligns with the typical synodic rotation period of the Sun at low latitudes. The findings demonstrate that sunspot tracking provides a simple and effective method for estimating the Sun’s rotation, making it well suited for educational and observational activities in astronomy.